Multicultural play therapy : making the most of cultural opportunities with children - Ray, Dee C.; Ogawa, Yumiko; Cheng, Yi-Ju (New York, NY : Routledge, 2022)
"Multicultural Play Therapy fills a wide gap in the play therapy literature. Each chapter helps expand cultural awareness, humility, and competence of play therapists so that they can work more effectively with children of diverse cultures, races, and belief systems. The unique perspectives presented here provide play therapists and advanced students with concrete information on how to broach issues of culture in play therapy sessions, parent consultations, and in the play therapy field at large. The book includes chapters on multiple populations and addresses the myriad cultural background issues that emerge in play therapy, and the contributors include authors from multiple races, ethnicities, cultural worldviews, and orientations"--
Keywords: Play therapy; Play therapy -- Cross-cultural studies; EDUCATION / Counseling / General; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Mental Health